Mantra Sasak: Klasifikasi, Fungsi, dan Penggunaannya oleh Masyarakat Desa Ganggelang - Lalu Fakihuddin; Gita Sarwadi (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purposes of this research are: (1) To classify the Sasak verbal-spells based on the variations of the language being used and the purpose of its implementation; and (2) to describe the function and its usage for the Sasak people in general and Ganggelang villagers, North Lombok in particular. This research uses a qualitative research method that both descriptive-interpretative. One of the reasons for choosing such a method is because it is compatible with the purpose of this research which is to document and describe the usage of Sasak verbal-spells. The data are collected by interviewing informants and gathering the results of the verbal-spells, its usage, and function by the Sasak people. To classify the data based on the language medium, a hermeneutic approach has been employed. The data analysis refers to perspective-constructivist model, that is directed by the intentions, categories that have been determined, and hypotheses that are aimed to be achieved. The result of this research, which is the verbal-spells then analyzed based on the language such as Arabic (verbal and written) spells, mixed between Sasak and Arabic spells, and Balinese spells or known as Puji Bali. Based on its purpose of implementation, Sasak verbal-spells are categorized into for healing purposes, Senggeger: a type of voodoo to attract the loved ones, Seasih-asih: to make one falls in love, supernatural power, and draining someone’s (physical) energy/power. Based on its function and practical usage, the Sasak verbal-spells have functions as healing/preventing diseases, to Seasih-asih purposes, to Senggeger/sencolet purposes, as a medium to ease childbirth processes, to counter other’s spells (sengkeles), and to counter possible dangers or destructions (sepenebeng/ajian kekebalan) and to drain someone’s energy.